Patterns of Frequently Diagnosed Pediatric Morbidities in Hospitalized Children in the Volta Region of Ghana - Samuel Mawuli Adadey MPHIL; Richmond Ayee MPHIL; Sylvester Languon MSC; Darius Quansah BSC; Osbourne Quaye PHD (SAGE Publishing, 2019)
Background . The aim of this study was to identify the frequently diagnosed pediatric diseases in the Volta Region of Ghana, as well as to examine the burden of these diseases. The top pediatric diseases that were frequently diagnosed were malaria, gastroenteritis, systemic infection, anemia, pneumonia, and respiratory tract infection. Methods . Clearance was obtained from the Volta Regional Directorate of the Ghana Health Service to collect primary data on pediatric hospitalizations in the major hospitals in the Region. Diseases with more than 1000 recorded cases of hospitalizations were considered among the top frequently diagnosed childhood morbidities. Results . The data suggest that the Northern sector had different seasonal patterns of recorded diagnosed pediatric cases compared with the Central and Southern sectors, which had similar patterns of the reported diseases. Most of the pediatric diseases in the Volta Region were more prevalent during the dry seasons compared with the rainy seasons and resulting in seasonal patterns of hospitalizations. Conclusion . Although the frequently diagnosed pediatric diseases can be prevented and/or treated, many children are hospitalized, with a proportion of them dying. It is, therefore, important that efforts are made to reduce the burden of pediatric hospitalization.